Central white matter integrity alterations in 2-3-year-old children following prenatal alcohol exposure. (1st August 2021) - Roos, Annerine; Wedderburn, Catherine J.; Fouche, Jean-Paul; Subramoney, Sivenesi; Joshi, Shantanu H.; Woods, Roger P.; Zar, Heather J.; Narr, Katherine L.; Stein, Dan J.; Donald, Kirsten A.
Highlights: Prenatal alcohol exposure alters white matter integrity in 2–3-year-old children. Effects of prenatal alcohol exposure on white matter integrity persist. Co-exposure of alcohol and tobacco amplify white matter alterations in motor tracts. Abstract: Background: Prenatal alcohol exposure (PAE) remains a potentially preventable, but pervasive risk factor to neurodevelopment. Yet, evidence is lacking on the impact of alcohol on brain development in toddlers. This study aimed to investigate the impact of PAE on brain white matter integrity in 2–3-year-old children. Methods: Children (n = 83, 30–37 months old) of the Drakenstein Child Health Study birth cohort, underwent diffusion MRI on a 3 T Siemens scanner during natural sleep. Parameters were extracted in children with PAE (n = 25, 56 % boys) and unexposed controls (n = 58, 62 % boys) using Tract-based Spatial Statistics, and compared by group. The contribution of maternal tobacco smoking to white matter differences was also explored. Results: Children with PAE had altered fractional anisotropy, radial diffusivity and axial diffusivity in brain stem, limbic and association tracts compared to unexposed controls. Notably lower fractional anisotropy was found in the uncinate fasciculus, and lower mean and radial diffusivity were found in the fornix stria terminalis and corticospinal tract (FDR corrected p < 0.05). There was a significant interaction effect of PAE and prenatal tobacco exposure which lowered mean, radial and axial diffusivity in the corticospinal tract significantly in the PAE group but not controls. Conclusion: Widespread altered white matter microstructural integrity at 2–3 years of age is consistent with findings in neonates in the same and other cohorts, indicating persistence of effects of PAE through early life. Findings also highlight that prenatal tobacco exposure impacts the association of PAE on white matter alterations, amplifying effects in tracts underlying motor function.